Analisis Sentimen SEA Games 2023 di Twitter Metode dengan Machine Learning - Irsyad, Akhmad; Geralda, Raihan Daiva; Wardhana, Reza (Mulawarman University, 2023)
Sentiment analysis is a method used to analyze and identify the polarity (positive, negative, or neutral) of text or data related to a user's thoughts, opinions, or emotions. This method is widely used in various fields, including sentiment analysis on social media data. One very popular social media platform is Twitter. One of the biggest sporting events in Asia is the SEA Games, which are held every two years. SEA Games, many Indonesians expressed their opinions, support and emotions regarding the 2023 SEA Games on Twitter. Using supervised learning methods can provide valuable insight into how Indonesian society responds and reacts to this important sporting event. The results of this analysis can help related parties, including organizers and sponsors of the 2023 SEA Games, in understanding public sentiment, evaluating performance, and making better decisions in order to organize a successful sporting event. The results of the trials carried out by the SVM method had the best performance with an F-1 score of 61.53%.